ANALISA BATAS KEWENANGAN BHABINKAMTIBMAS DALAM PENGAWASAN ANGGARAN DANA DESA - M. Dawud Rizkyandi; Taufiqurrahman Taufiqurrahman; Firzhal Arzhi Jiwantara (Jurnal Ilmiah Hospitality, 2022)
The police is one of the functions of the state government in the field of maintaining security and public order, upholding the law, and providing protection, stability and community service in order to maintain domestic security, in the implementation of the task of implementing police partnerships with the community is very important in smoothly implementing police objectives in their duties, namely the maintenance of security and order in the community, methods that Used is a normative legal research method with a regulatory approach and conceptual approach, in this study willdescribe the form of authority and what can be done by the police, especially bhabinkamtibas in an effort to control the budget, supervision is carried out so as not to achieve abuse of authority so that the achievement of village welfare is far from the occurrence of corruption collusion and nepotism